Adhesion to fibronectin stimulates proliferation of wild-type and bcr/abl-transfected murine hematopoietic cells - Krämer, Alwin; Hörner, Susanne; Willer, Andreas; Frühauf, Stefan; Hochhaus, Andreas; Hallek, Michael; Hehlmann, Rüdiger (Proceedings of the National Academy of Sciences of the United States of America, 1999)
Cells of most tissues require adhesion to a surface to grow. However, for hematopoietic cells, both stimulation and inhibition of proliferation by adhesion to extracellular matrix components have been described. Furthermore, it has been suggested that progenitor cells from chronic myelogenous leukemia show decreased β1 integrin-mediated adhesion to fibronectin, resulting in increased proliferation and abnormal trafficking. However, we show here that the chronic myelogenous leukemia-specific fusion protein p210bcr/abl stimulates the expression of α5β1 integrins and induces adhesion to fibronectin when expressed in the myeloid cell line 32D.